Analisis Kemampuan Self Regulation Siswa pada Pembelajaran Sains saat PJJ Online di Era Pandemi Covid-19 - Setyaningrum, Novalina; Rubini, Bibin; Ardianto, Didit (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2021)
This study aims to determine students' self regulation during the Covid-19 pandemic at islamic senior high school in Kabupaten Karawang, West Java. The research method used descriptive method and data collection techniques using a survey through Google Form. The research subjects were Grade X,XI,XII . The results showed that the skill of students’ self regulation was in the high category with presentage of 17%, medium category 69% and high catogory 14%. Based on three components of self-regulation, majority of students were in medium category (cognitive 66%, behavior 62% dan motivation 50%). Analysis also have done to measure the skill of students’ self regulation before and after online learning. Majority of the students were ini medium category (preparation 76%, implementation 53%, reflection 64%). The result of the reasearch show that the students need more effort to enhance the skill of self regulation, to be success in online learning.